2019
DOI: 10.1002/ejic.201900550
|View full text |Cite
|
Sign up to set email alerts
|

Single Source Precursors for Calcium Sulfide (CaS) Deposition

Abstract: Here we describe preliminary studies into the synthesis structural characterisation and thermal properties of a family of calcium xanthate precursors for application in the deposition of CaS thin films. The straightforward, low‐temperature syntheses are detailed along with characterisation of the resulting compounds by 1H and 13C NMR and elemental analysis. Solid state molecular structures of all compounds, obtained from single‐crystal X‐ray diffraction, are presented and discussed in detail. The decomposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Synthetic routes to these materials are being developed and one approach is the use of SSPs. 534 In the mid-1990s, Purdy and George described the synthesis of a range of calcium DTC complexes, [Ca(S 2 CNR 2 ) 2 ], including those derived from primary amines, together with the strontium complex, [Sr(S 2 CNBu 2 ) 2 ], from reactions of [M-(NH 2 ) 2 ] with CS 2 in the presence of secondary amines. 535 TGA showed that disubstituted complexes decompose at high temperatures (350−400 °C) to give highly carbonized CaS, and [Sr(S 2 CNBu 2 ) 2 ] has a similar decomposition profile to afford SrS.…”
Section: Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic routes to these materials are being developed and one approach is the use of SSPs. 534 In the mid-1990s, Purdy and George described the synthesis of a range of calcium DTC complexes, [Ca(S 2 CNR 2 ) 2 ], including those derived from primary amines, together with the strontium complex, [Sr(S 2 CNBu 2 ) 2 ], from reactions of [M-(NH 2 ) 2 ] with CS 2 in the presence of secondary amines. 535 TGA showed that disubstituted complexes decompose at high temperatures (350−400 °C) to give highly carbonized CaS, and [Sr(S 2 CNBu 2 ) 2 ] has a similar decomposition profile to afford SrS.…”
Section: Groupmentioning
confidence: 99%
“…Consequently, as a result of their high QYs and resistance to photobleaching, thin films of lanthanide-doped calcium sulfide nanomaterials show potential as fluorescent materials for displays, imaging and solar spectral conversion. Synthetic routes to these materials are being developed and one approach is the use of SSPs …”
Section: Binary Sulfidesmentioning
confidence: 99%
“…Molecular seven-coordinate calcium compounds have recently been synthesized as precursors for e.g. CaS, which is among the alkaline earth sulfides (MgS, CaS, SrS, BaS) that are interesting materials for emissive layer matrices in thin-film electroluminescent displays when doped with other elements [72]. Xanthate complexes can be stabilized with neutral donor ligands like ethanol, N,N,N 0 ,N 00 ,N 00 -pentamethyldiethylenetriamine (PMDTA) or substituted pyridines, and the coordination geometries reach from (distorted) pentagonal bipyramidal to distorted capped prismatic (Fig.…”
Section: Calciummentioning
confidence: 99%
“…Heptacoordinated calcium xanthate compounds with pyridine-derived co-ligands can act as precursors for CaS (with permission from[72]). Disila polyether complexes with Ca 2+ , Sr 2+ and Ba 2+ (adapted with permission from[73]).…”
mentioning
confidence: 99%
“…193 Using different precursors simultaneously does, however, lead to complications associated with differing thermal decomposition rates and temperatures, solubilities and volatilities, and different film deposition mechanisms leading to varied growth rates; all of which will contribute towards non-homogeneous and nonstoichiometric deposition. 218,255,256 While stoichiometries can be improved by trial-and-error depositions to find the right precursor ratio, non-homogeneous deposition can only be fixed by using more compatible precursors with similar pertinent properties.…”
Section: Metal Oxides and Chalcogenidesmentioning
confidence: 99%